Antarctic krill 454 pyrosequencing reveals chaperone and stress transcriptome - Toullec, Jean-Yves; Meng, Yan; Guan, Leluo; Clark, Melody S.; Moore, Stephen S.; Thorne, Michael A. S.; Peck, Lloyd S. (2011)
Background The Antarctic krill Euphausia superba is a keystone species in the Antarctic food chain. Not only is it a significant grazer of phytoplankton, but it is also a major food item for charismatic megafauna such as whales and seals and an important Southern Ocean fisheries crop. Ecological data suggest that this species is being affected by climate change and this will have considerable consequences for the balance of the Southern Ocean ecosystem. Hence, understanding how this organism functions is a priority area and will provide fundamental data for life history studies, energy budget calculations and food web models. Methodology/Principal Findings The assembly of the 454 transcriptome of E. superba resulted in 22,177 contigs with an average size of 492bp (ranging between 137 and 8515bp). In depth analysis of the data revealed an extensive catalogue of the cellular chaperone systems and the major antioxidant proteins. Full length sequences were characterised for the chaperones HSP70, HSP90 and the super-oxide dismutase antioxidants, with the discovery of potentially novel duplications of these genes. The sequence data contained 41,470 microsatellites and 17,776 Single Nucleotide Polymorphisms (SNPs/INDELS), providing a resource for population and also gene function studies. Conclusions This paper details the first 454 generated data for a pelagic Antarctic species or any pelagic crustacean globally. The classical “stress proteins”, such as HSP70, HSP90, ferritin and GST were all highly expressed. These genes were shown to be over expressed in the transcriptomes of Antarctic notothenioid fish and hypothesized as adaptations to living in the cold, with the associated problems of decreased protein folding efficiency and increased vulnerability to damage by reactive oxygen species. Hence, these data will provide a major resource for future physiological work on krill, but in particular a suite of “stress” genes for studies understanding marine ectotherms' capacities to cope with environmental change.